PENGARUH KERJASAMA TIM DAN PELATIHAN KERJA TERHADAP KEPUASAN KERJA PEGAWAI BPBD KOTA BONTANG - Ayu Dita Sari; Alda Andika; Isdayanti Isdayanti (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
This study aims to determine the effect of teamwork and job training on employee job satisfaction among Bontang City Badan Penanggulangan Bencana Daerah (BPBD) employees. This research method is descriptive-quantitative, using data collection techniques such as observation, documentation, questionnaires, and interviews. The population in this study were Bontang City BPBD employees. The sampling technique in this research used saturated samples with a sample of 50 respondents. The analysis technique used is multiple linear regression analysis with the SPSS version 16 application. The results of this research show that from the results of partial test calculations or t tests on team collaboration, the results obtained are t count 12.142 > t table 2.011 and work training t count 3.759 > t table 2.011 with a significance of 0.00 <0.05. The results of the simultaneous test, or F test, in this study obtained a calculated F of 77.674 > F table 3.20 with a significance of 0.00 < 0.05. From the results of the T and F tests, it was found that teamwork and job training had a partial and significant effect on the job satisfaction of Bontang City BPBD employees.Â Keywords: Job Satisfaction, Job Training, Teamwork